Interrelation of Communicative Speech Competence and Prosocial Behavior of Students - Oksana Chaikovska; Liudmyla Melnyk; Liubov Kuzo (Insight: the psychological dimensions of society, 2023)
The article presents the results of theoretical and empirical analysis of the influence of communicative speech competence on the development of prosocial behavior of future specialists in the field of sociology. The purpose of the research is to study the interrelation between the level of development of communicative speech competence and prosocial behavior of students. Methods used in the study: analysis of scientific sources, observations, surveys to determine the level of development of communicative competence and prosocial behavior, methods of mathematical statistics. Results. The peculiarities of the development of communicative control in communication, the level of communicative competence, speech competence, the level of empathic abilities, prosocial tendencies of professional competencies of students at different stages of study: the first year (the stage of entering the profession) and the sixth year of study (obtaining a complete higher education) are revealed in the course of the research. The findings demonstrate a positive correlation between the level of communicative speech training among the first-year students and their indicators of empathic abilities and altruistic tendencies in prosocial behavior. Moreover, an inverse relationship was observed between the level of communicative speech training and the inclination towards conformity and compliance. Among the master’s students, a positive association is evident between enhanced communicative speech training and heightened levels of empathy and compliant prosocial tendencies. Conversely, an inverse relationship is observed between communicative speech training and emotionality and altruism, as well as a reduced inclination towards providing assistance to individuals in need of emotional support and selfless charitable help. Statistically significant differences in the level of communicative speech competence and the development of empathic tendencies are identified between the firstyear and sixth-year student groups, with the latter exhibiting higher levels. Discussion and conclusions. It is argued that raising the level of communicative characteristics of socionomic students significantly influences the manifestation of prosocial tendencies. It is suggested that the educational training of socionomic professionals does not entirely bridge the existing gap between personal and professional development of students. The identified influence of the development of communicative speech competence on the formation of socionomic students’ prosocial behavior points to the necessity of further research on the development of the communicative speech component in the training of psychologists and social workers.